The Relationship Between Total Quality Management (Tqm) Practices, Service Quality, Market Orientation, And Organizational Performance - Samat, Nusrah (2004)
Organizations, both manufacturing and service have realized the importance of quality. Therefore, they have been influenced by some quality programs related to Total Quality Management (TQM). TQM is always said to provide a lot of benefits to the organization. One of them is better service quality, which is crucial for service organizations in satisfying customers' needs and wants.